Academic Senate Minutes 2009-03-05 - Academic Senate:::::::::
Election results. Report from the Ad-Hoc Diversity Committee on diversity activities. Agenda approved. Minutes of 2/5 and 2/19 approved. Update on WASC. Vice President of SAEM report. Associated Students Report. Chair-Elect Report. Statewide Senators Report. Resolution Affirming the Standing of Sonoma State University Professors Emeritus Approved. Resolution in Support of Low Cost Books for Students – First Reading. APC Report. SAC Report. EPC Report. Revision to the Excellence in Teaching Award – First Reading. Good of the Order.